2020
DOI: 10.18203/2394-6040.ijcmph20204373
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of mandatory glaucoma screening in all patients from outreach cataract camps referred to a base hospital for cataract surgery

Abstract: Background: Glaucoma is the first cause of irreversible blindness and second leading cause of visual loss in the world. The purpose of this study was to conduct mandatory glaucoma screening and to find out the prevalence of glaucoma, in all patients referred for cataract surgery to a base hospital. Methods: A retrospective analysis was conducted of all patients referred from rural screening camps to base hospital for cataract surgery. Medical records of 5024 consecutive patients referred to base hospital from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The prevalence of glaucoma seems to vary from 2.6% to 3.45% in rural population >40 years as from different studies in India, all of the studies being conducted in the pre-COVID period [8][9][10][11]. Tomar et al [7] reported that the prevalence of glaucoma in patients with cataract was found to be 3.7%. In our study, with similar subjects, the prevalence rate of glaucoma is amplified in the post-COVID period (3.8%) as compared to the pre-COVID period (2.9%), but it is not statistically significant (>0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of glaucoma seems to vary from 2.6% to 3.45% in rural population >40 years as from different studies in India, all of the studies being conducted in the pre-COVID period [8][9][10][11]. Tomar et al [7] reported that the prevalence of glaucoma in patients with cataract was found to be 3.7%. In our study, with similar subjects, the prevalence rate of glaucoma is amplified in the post-COVID period (3.8%) as compared to the pre-COVID period (2.9%), but it is not statistically significant (>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic criterion for glaucoma was done according to the International Society of Geographical and Epidemiological Ophthalmology (ISGEO) recommendations with certain study-specific definitions [6][7][8][9] (a) Ocular hypertensive IOP >21 mmHg, (b) Disc suspect -VCDR >0.5, asymmetry of cup-disc ratio 9. Primary angle-closure suspect: Presence of occludable angle.…”
Section: Priyambada Et Almentioning
confidence: 99%